Bedside Burr Hole for Intracranial Pressure Monitoring Performed by Pediatric Intensivists in Children With CNS Infections in a Resource-Limited Setting: 10-Year Experience at a Single Center. Issue 5 (June 2015) - Singhi, Sunit; Kumar, Ramesh; Singhi, Pratibha; Jayashree, Muralidharan; Bansal, Arun
Abstract : Objective: Intracranial pressure monitoring can help in early identification of raised intracranial pressure and in setting more informed goals for treatment. We describe our 10-year experience of bedside burr holes performed by pediatric intensivists to establish intracranial pressure monitoring in children with CNS infections in a resource-limited setting and the technical difficulties and complications encountered. Design: Descriptive study of prospectively recorded data. Setting: PICU of a tertiary care academic institute. Patients: Consecutive comatose patients with raised intracranial pressure who underwent intracranial pressure monitoring from 2004 to 2013. Intervention: An intraparenchymal (1.2 mm) or an intraventricular transducer (3.4 mm) (Codman) was placed by a pediatric intensivist through a micro burr hole using a standard protocol. Technical difficulties during the procedure and complications were recorded. Measurements and Main Results: Over 10 years, 265 intracranial pressure catheters were placed in 259 patients, mainly for acute CNS infections ( n = 242, 93.4%). Median age of patients was 4.8 years, youngest being 6 weeks; 21 patients (8.1%) were younger than 1 year. Intraparenchymal transducer was used in 252 patients (97.3%). Median (interquartile range) duration of intracranial pressure monitoring was 96 hours (72–144 hr). Complications were seen in 3.5% of patients ( n = 9/259); the incidence was 0.28 per 1, 000 hours of intracranial pressure monitoring. Procedure-related ventriculitis occurred in three of seven patients (42.8%) with intraventricular catheter, in contrast to none in patients with intraparenchymal transducer. Overall mortality was 32.8% ( n = 85). On Cox-regression analysis, "blood component therapy" was an independent predictor of poor outcome defined as death or severe neurodisability (adjusted hazard ratio, 1.58; 95% CI, 1.16–2.16; p = 0.004). Conclusions: In a resource-limited setting, pediatric intensivists can safely and successfully perform burr holes at bedside for establishing intraparenchymal intracranial pressure monitoring in children with acute CNS infections. However, our data do not support placement of ventriculostomy catheters by pediatric intensivists in similar settings.